Reducing broad-spectrum antibiotic use in intensive care unit between first and second waves of COVID-19 did not adversely affect mortality. (June 2022) - Chan, X.H.S.; O'Connor, C.J.; Martyn, E.; Clegg, A.J.; Choy, B.J.K.; Soares, A.L.; Shulman, R.; Stone, N.R.H.; De, S.; Bitmead, J.; Hail, L.; Brealey, D.; et al.
Summary: Background: The COVID-19 pandemic increased the use of broad-spectrum antibiotics due to diagnostic uncertainty, particularly in critical care. Multi-professional communication became more difficult, weakening stewardship activities. Aim: To determine changes in bacterial co-/secondary infections and antibiotics used in COVID-19 patients in critical care, and mortality rates, between the first and second waves. Methods: Prospective audit comparing bacterial co-/secondary infections and their treatment during the first two waves of the pandemic in a single-centre teaching hospital intensive care unit. Data on demographics, daily antibiotic use, clinical outcomes, and culture results in patients diagnosed with COVID-19 infection were collected over 11 months. Findings: From March 9 th, 2020 to September 2 nd, 2020 (Wave 1), there were 156 patients and between September 3 rd, 2020 and February 1 st, 2021 (Wave 2) there were 235 patients with COVID-19 infection admitted to intensive care. No significant difference was seen in mortality or positive blood culture rates between the two waves. The proportion of patients receiving antimicrobial therapy (93.0% vs 81.7%; P < 0.01) and the duration of meropenem use (median (interquartile range): 5 (2–7) vs 3 (2–5) days; P  = 0.01) was lower in Wave 2. However, the number of patients with respiratory isolates of Pseudomonas aeruginosa (4/156 vs 21/235; P < 0.01) and bacteraemia from a respiratory source (3/156 vs 20/235; P < 0.01) increased in Wave 2, associated with an outbreak of infection. There was no significant difference between waves with respect to isolation of other pathogens. Conclusion: Reduced broad-spectrum antimicrobial use in the second wave of COVID-19 compared with the first wave was not associated with significant change in mortality.